Autosomal Dominant Pseudohypoaldosteronism Type 1 in an Infant with Salt Wasting Crisis Associated with Urinary Tract Infection and Obstructive Uropathy - Sasigarn A. Bowden; Corin Cozzi; Scott E. Hickey; Devon Lamb Thrush; Caroline Astbury; Sushma Nuthakki (Case Reports in Endocrinology)
Type 1 pseudohypoaldosteronism (PHA1) is a salt wasting syndrome caused by renal resistance to aldosterone. Primary renal PHA1 or autosomal dominant PHA1 is caused by mutations in mineralocorticoids receptor gene (NR3C2), while secondary PHA1 is frequently associated with urinary tract infection (UTI) and/or urinary tract malformations (UTM). We report a 14-day-old male infant presenting with severe hyperkalemia, hyponatremic dehydration, metabolic acidosis, and markedly elevated serum aldosterone level, initially thought to have secondary PHA1 due to the associated UTI and posterior urethral valves. His serum aldosterone remained elevated at 5 months of age, despite resolution of salt wasting symptoms. Chromosomal microarray analysis revealed a deletion of exons 3–5 in NR3C2 in the patient and his asymptomatic mother who also had elevated serum aldosterone level, confirming that he had primary or autosomal dominant PHA1. Our case raises the possibility that some patients with secondary PHA1 attributed to UTI and/or UTM may instead have primary autosomal dominant PHA1, for which genetic testing should be considered to identify the cause, determine future recurrence risk, and possibly prevent the life-threatening salt wasting in a subsequent family member. Future clinical research is needed to investigate the potential overlapping between secondary PHA1 and primary autosomal dominant PHA1.